Implementation of Problem Based Learning Method to Improve Reading Skills in Fifth Grade Students of SDN 3 Sila - Rezki Amelia; Abdussahid; Fuaddudin (Lembaga Bale Literasi, 2026)
The objectives of this study are: 1) to represent the application of the Problem Based Learning model in developing reading skills; 2) to develop reading skills with the Problem Based Learning model. Classroom Action Research (CAR) is a qualitative research. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 25 female students. The data collection system used was observation, documentation, and tests with triangulation validity testing of sources and techniques. The Miles and Huberman model was used for data analysis. The results showed that students' reading ability in the pre-action period reached an average of 59.60 with classical completeness of 32%. Cycle 1 reached an average of 65.5 with classical completeness of 52%. Cycle 2 obtained an average value of 76.40 and classical completeness of 72%. Based on these facts, it can be said that the reading ability of fifth-grade students of SDN 3 Sila can be improved by using the Problem Based Learning model.